Inhalation technique in asthma in children: could an intensive summer educational camp improve it? - Pecoraro, Luca; Norato, Alessia; Accorsi, Paola; Dalle Carbonare, Luca; Piacentini, Giorgio; Pietrobelli, Angelo (Acta Biomedica Atenei Parmensis, 2022)
BACKGROUND AND AIM: Asthma camp is a summer camp involving children with asthma. It is demonstrated that the experience of asthma camp is related to an overall improvement in clinical outcome related to asthma and also in pMDI technique. Based on this observation, we made up a 3-days intensive asthma summer camp training the children every day using a standard protocol that included step-by-step instructions for the correct use of pMDI and spacer with a mouthpiece. The aim of this first preliminary prospective study was to evaluate the impact that a structured short-term educational asthma camp could have on performance in the use of pMDI and spacer by the children involved.METHODS: Ten children with asthma attended a 3-days educational camp program. A pediatric allergologist made assessments of the inhalation technique for each child at the beginning and the end of the 3-days asthma summer camp.RESULTS: 7 patients were evaluated. The median age was 129 months (range 92-153 months). The median value of the modified MDI use score (mMus) was 8 at the beginning of the asthma summer and 10 at the end of the asthma summer camp was 10. The overall improvement in inhalation technique was +25%.CONCLUSIONS: This is the first preliminary prospective study demonstrating that a 3-days intensive asthma summer camp is related to an overall improvement in pMDI technique in children affected by asthma. It represents another evidence that asthma summer camp is a fundamental instrument to improve asthma education and management in childhood asthma.